Intersectorial integration in Malaysian economic transition and change: A cointegration analysis - Tuck, Cheong Tang (Universiti Utara Malaysia, 2002)
The present study investigates empirically the inter-sector integration in Malaysian economic transition and change over the period 1960-1998. It is obvious that all the economic sectors moved together over time and none of them developed in its own way. The interest GDP (Gross Domestic Product) sectors are outputs of agriculture, manufacturing, and services. The results of cointegration analysis (Pesaran et.al., 2001) find no long run equilibrium relationship among these sectors. In the short run, the agriculture output influences the manufacturing output, and affects services output negatively. The manufacturing sector has little influence on agriculture output. The implications that can be drawn are that long-term structural and integrated policies are necessary to bring back the sectors' disequilibrium in economy. It can be implemented through sound fiscal and monetary policies. In addition, promoting agriculture sector growth is needed because any increase in agricultural output might have positive and sizeable effects on the manufacturing output.